2020
DOI: 10.1111/jdi.13248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ipragliflozin on the development and progression of kidney disease in patients with type 2 diabetes: An analysis from a multicenter prospective intervention study

Abstract: Aims/Introduction Type 2 diabetes mellitus is the leading cause of kidney failure worldwide, but few effective long‐term treatments are available. Methods This was an investigator‐initiated multicenter prospective intervention study in which ipragliflozin (50 mg) was administered once daily, and glycemic control, estimated glomerular filtration rate (eGFR) and adverse events were evaluated until 104 weeks after starting research. Results There were 407 patients analyzed. In the eGFR ≥90 group and eGFR ≥60 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…IAD-eGFR in affected patients with reduced eGFR is still unknown. A recent small-scale prospective study reported that IAD-eGFR in CKD stage 3b patients was not particularly observed and did not cause a significant decrease [18], and a sub-analysis of the CREDENCE study showed that IAD-eGFR was not significantly observed, and they reported that the changes in eGFR were the smallest in CKD stage 3b patients [19]. In the real world data from our Figure 5.…”
Section: Discussionmentioning
confidence: 53%
“…IAD-eGFR in affected patients with reduced eGFR is still unknown. A recent small-scale prospective study reported that IAD-eGFR in CKD stage 3b patients was not particularly observed and did not cause a significant decrease [18], and a sub-analysis of the CREDENCE study showed that IAD-eGFR was not significantly observed, and they reported that the changes in eGFR were the smallest in CKD stage 3b patients [19]. In the real world data from our Figure 5.…”
Section: Discussionmentioning
confidence: 53%
“…Маловероятно, что этот феномен можно объяснить высокой частотой выбывания среди пациентов с исходной рСКФ <60 мл/мин/1,73 м 2 , поскольку в соответствии с анализом в подгруппах в основной публикации результатов исследования STELLA-LONG TERM доля пациентов с исходным нарушением функции почек, прекративших или временно прервавших лечение, составила лишь 12,57% (24/191) [27]. Более того, результаты недавнего проспективного многоцентрового исследования длительностью 104 нед, выполненного в Японии, у пациентов с СД2, получающих ипраглифлозин 50 мг/сут, свидетельствуют о способности ипраглифлозина улучшать рСКФ у пациентов с исходно низкой рСКФ [29]. В настоящем анализе у пациентов с исходной рСКФ ≥60 мл/мин/1,73 м 2 (2-я категория), наоборот, отмечено стойкое значимое снижение рСКФ через 3 года; однако средняя рСКФ в этой контрольной точке (82,03 мл/мин/1,73 м 2 ) оставалась ≥60 мл/мин/1,73 м 2 .…”
Section: Discussionunclassified
“…В настоящем анализе у пациентов с исходной рСКФ ≥60 мл/мин/1,73 м 2 (2-я категория), наоборот, отмечено стойкое значимое снижение рСКФ через 3 года; однако средняя рСКФ в этой контрольной точке (82,03 мл/мин/1,73 м 2 ) оставалась ≥60 мл/мин/1,73 м 2 . Полученный результат подтверждает эффект снижения рСКФ у пациентов с клубочковой гиперфильтрацией на фоне терапии ипраглифлозином; это наблюдение также подтверждают результаты 104-недельного многоцентрового исследования ипраглифлозина [29].…”
Section: Discussionunclassified
“…A post hoc analysis of the CREDENCE trial showed that the effects of canagliflozin on renal and safety outcomes in participants from eastern and southeastern Asian (EA) countries were generally similar to those of the non‐EA participants 8 . In addition, in Japanese patients with diabetes, ipragliflozin corrected hyperfiltration in the patients with high eGFR (eGFR ≥60), while it increased eGFR in patients with a low eGFR (30≤eGFR<60 mL/min/1.73 m 2 ) 9 . Furthermore, an observational study provided real‐world evidence that SGLT2 inhibitors slowed the eGFR decline rate in Japanese patients with DKD 10 .…”
Section: Figurementioning
confidence: 98%